December 2022 QDL Users Survey Results - Marcin Werla (13761781) (2023)
This presentation summarises the Qatar Digital Library users survey conducted in December 2022. This survey was conducted to gain insights into the QDL’s primary content database and classify its users into various groups, to learn which QDL resources are being used the most by various user groups, to identify user groups that require focused outreach and engagement and identify underutilized resources, as well as to gauge user sentiment towards QDL. The total number of responses in the survey was 387. During the survey period, the overall number of QDL users measured by Google Analytics was 17,106. Therefore, the sample size is sufficient to have a confidence level of 95% that the real value is within ±5% of surveyed values.